Fat man and little boy - Newman, Paul, 1925-; Schultz, Dwight; Bedelia, Bonnie, 1946-; Cusack, John. (Hollywood, CA : Paramount, 1990)
Fat man and little boy were the names given to the first 2 atomic bombs built by "The Manhattan Project". This film is the true story of their creation, and the fascinating people involved.
VHS format.
"32252"
Videocassette release of the 1989 motion picture.
Rated PG-13.
Closed captioned for the hearing impaired.
In stereo.
Keywords: Manhattan Project (U.S.); Historical films; Atomic bomb; Video recordings for the hearing impaired